2017
DOI: 10.1161/hypertensionaha.117.09923
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deletion of Renin-b in the Brain Alters Drinking and Metabolism

Abstract: The brain specific isoform of renin (Ren-b), has been proposed as a negative regulator of the brain renin-angiotensin system (RAS). We analyzed mice with a selective deletion of Ren-b which preserved expression of the classical renin (Ren-a) isoform. We reported that Ren-bNull mice exhibited central RAS activation and hypertension through increased expression of Ren-a, but the dipsogenic and metabolic effects in Ren-bNull mice are unknown. Fluid intake was similar in control and Ren-bNull mice at baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Cellular and molecular studies have reported that all RAS genes and their promoter regions are active in the brain, while other evidences also revealed the de novo production of RAS components in the brain (Hermann et al, 1987;Fuxe et al, 1980). The establishment of brain RAS is also supported by several pharmacological inhibition studies (Shinohara et al, 2016(Shinohara et al, , 2017. Similarly, it has been found that all the components required for the synthesis of angiotensin peptides are synthesized locally within the brain (Harding et al, 1988).…”
Section: The Components Of Brain Renin Angiotensin Systemmentioning
confidence: 93%
See 1 more Smart Citation
“…Cellular and molecular studies have reported that all RAS genes and their promoter regions are active in the brain, while other evidences also revealed the de novo production of RAS components in the brain (Hermann et al, 1987;Fuxe et al, 1980). The establishment of brain RAS is also supported by several pharmacological inhibition studies (Shinohara et al, 2016(Shinohara et al, , 2017. Similarly, it has been found that all the components required for the synthesis of angiotensin peptides are synthesized locally within the brain (Harding et al, 1988).…”
Section: The Components Of Brain Renin Angiotensin Systemmentioning
confidence: 93%
“…However, van Thiel et al suggested that intracellular renin could be the key to generation of angiotensins in the brain, and coordinate other non-RAS functions (van Thiel et al, 2017). In addition, the impaired activity or expression of the brain renin may cause neurogenic hypertension, altering drinking and metabolism (Shinohara et al, 2016(Shinohara et al, , 2017. Few studies though still suggest that the expression of renin is controversial in the brain .…”
Section: Brain Renin/pro-reninmentioning
confidence: 99%
“…In vitro and in vivo experiments suggest this form of renin is indeed active (546,555,973). Nevertheless, the physiological significance of endogenous intracellular renin remains unclear because, surprisingly, deletion of renin-b caused hypertension and increased activity of the brain RAS (954,955).…”
Section: A Localization Of Ras Components In Brainmentioning
confidence: 99%
“…These data demonstrate that the secreted version of renin (Renin-a) is dispensable within the brain for cardiovascular, fluid, and metabolic homeostasis. Knockout of renin-b resulted in an increase in BP and sympathetic nerve activity and impaired baroreflex sensitivity as demonstrated by Shinohara et al [6]. These authors proposed the hypothesis that in the brain, renin-b inhibits renin-a expression under normal conditions.…”
Section: Renin and Prorenin Receptormentioning
confidence: 87%
“…Moreover, the authors showed an increase in Ang II activity in renin knockout mice, suggesting that Ang II formation might occur by other proteases, such as cathepsin [84,85]. In addition to the above cardiovascular effects, Shinohara et al [6] recently demonstrated that Renin-b is also important in the regulation of energy homeostasis and thermogenesis. The authors showed an increase in resting metabolic rate and SNA to brown adipose tissue in renin-b null mice.…”
Section: Renin and Prorenin Receptormentioning
confidence: 99%